Evaluación técnico financiera de la utilización de un surfactante en la biorremediación de lodos aceitosos del Campo Castilla (2017)
In the following work, it is presented the geologic description and history of production of Campo Castilla. It is described the basic concepts in the process of biorremediation along with the principal laws that rule over the management of oil waste in Colombia. Afterwards a comparison between the biorremediation process used by the company and the propossed method with the use of a surfactant is done to finally perform an economic analysis leading to the conclusion of which method is more attractive from the economic point of view to the company.